Ensino de Ciências por investigação nos anos iniciais do Ensino fundamental: estudo dos conceitos básicos de eletricidade para a promoção da alfabetização científica - Azevedo, Lidiany Bezerra Silva de (2016)
The present study hasits purpose realize aresearch about the physical knowledge in the early years of elementary school, having the main approachthe teaching of science for research, as an important didacticismstrategy for the promotion of Scientific Literacy. The choice of subject was given because of physical knowledge is little explored in the early years of schoolingwe believe that early the child must have contact with the teaching of physics, why this is something that is part of their daily lives. Therefore, we develop a didactic sequence addressing the Electricity contents, because the National Curriculum Parameters of Science Teaching consider important the presence of these contents in Primary Education. Therefore, the proposed research will be qualitative, type action research, developed on 11 to 12 November 2015 in a class of 5th grade of elementary school, with the research Locus a school in the municipality of Palmeira dos Índios. As data collection instrument we use questionnaires and audio recordings. For data analysis, we will use the content analysis categories of Bardin , as well as indicators of Scientific Literacy proposed by Sasseron and Carvalho. The results showed that the Education for research is a methodology that provides the student an effective learning and investigative practices help students to become literate scientifically.